In the Light of Postmodernism, Differentiating Between the Truth and Myth of Cleopatra’ Demise - Almas, Najia; Dr. Shumaila Mazhar (Journal of Peace, Development and Communication, 2023)
Duvall (2002) states that history literary history is different form the textually meditated and reconstructed history. I strongly believe that there is a strong line that defines the truth regarding history and its reconstructed parts. There would be need to explore two different worlds/era/time in order to search for the real incident that occurred in the past. This is also the essence of the postmodernism which always finds a connectivity of the present to its past. Thus, this is the aim of this paper to separate the truth from the myth that lurked on Cleopatra’s demise for almost two thousand years.